MAGE‐C3 promotes cancer metastasis by inducing epithelial‐mesenchymal transition and immunosuppression in esophageal squamous cell carcinoma. Issue 12 (4th August 2021) - Wu, Qingnan; Zhang, Weimin; Wang, Yan; Min, Qingjie; Zhang, Hongyue; Dong, Dezuo; Zhan, Qimin
Abstract: Background: Evading immune surveillance is necessary for tumor metastasis. Thus, there is an urgent need to better understand the interaction between metastasis and mechanisms of tumor immune evasion. In this study, we aimed to clarify a novel mechanism that link tumor metastasis and immunosuppression in the development of esophageal squamous cell carcinoma (ESCC). Methods: The expression of melanoma‐associated antigen C3 (MAGE‐C3) was detected using immunohistochemistry. Transwell assays were used to evaluate the migration and invasion ability of esophageal squamous cell carcinoma (ESCC) cells. Metastasis assays in mice were used to evaluate metastatic ability in vivo . Lymphocyte‐mediated cytotoxicity assays were performed to visualize the immune suppression function on tumor cells. RNA sequencing was performed to identify differentially expressed genes between MAGE‐C3 overexpressing ESCC cells and control cells. Gene ontology (GO) enrichment analyses was performed to identify the most altered pathways influenced by MAGE‐C3. The activation of the interferon‐γ (IFN‐γ) pathway was analyzed using Western blotting, GAS luciferase reporter assays, immunofluorescence, and flow cytometry. The role of MAGE‐C3 in the IFN‐γ pathway was determined by Western blotting and immunoprecipitation. Furthermore, immunohistochemistry and flow cytometry analysis monitored the changes of infiltrated T cell populations in murine lung metastases. Results: MAGE‐C3 was overexpressed in ESCC tissues. High expression of MAGE‐C3 had a significant association with the risk of lymphatic metastasis and poor survival in patients with ESCC. Functional experiments revealed that MAGE‐C3 promoted tumor metastasis by activating the epithelial‐mesenchymal transition (EMT). MAGE‐C3 repressed antitumor immunity and regulated cytokine secretion of T cells, implying an immunosuppressive function. Mechanistically, MAGE‐C3 facilitated IFN‐γ signaling and upregulated programmed cell death ligand 1 (PDL1) by binding with IFN‐γ receptor 1 (IFNGR1) and strengthening the interaction between IFNGR1 and signal transducer and activator of transcription 1 (STAT1). Interestingly, MAGE‐C3 displayed higher tumorigenesis in immune‐competent mice than in immune‐deficient nude mice, confirming the immunosuppressive role of MAGE‐C3. Furthermore, mice bearing MAGE‐C3‐overexpressing tumors showed worse survival and more lung metastases with decreased CD8 + infiltrated T cells and increased programmed cell death 1 (PD‐1) + CD8 + infiltrated T cells. Conclusion: MAGE‐C3 enhances tumor metastasis through promoting EMT and protecting tumors from immune surveillance, and could be a potential prognostic marker and therapeutic target. Abstract : Our results identified that MAGE‐C3 promotes tumor metastasis not only through the EMT but also by protecting tumors from immunosurveillance